2017
DOI: 10.1111/apa.13993
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of cognitive and educational outcomes of those born small for gestational age

Abstract: AimThis study examined the long‐term cognitive and educational outcomes of being born small for gestational age (SGA) and assessed whether the family's attitude towards education modified the effect of being born SGA on educational attainment.MethodsWe used anonymised data on 9598 individuals from the Stockholm Birth Cohort. This study focused on babies born in 1953 in the Stockholm metropolitan area, who were followed up for 50 years, and included educational data at the age of 13 and 48. Ordinary least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Our finding of impaired cognitive development is supported by earlier studies showing decreased learning and memory associated with LBW in pigs ( 17 , 18 ). Similarly, LBW in humans has been shown to cause learning difficulties throughout adolescence ( 6 , 7 ), as well as impaired spatial learning ( 47 ). However, there have also been studies which have shown LBW pigs to have a comparable, or even superior, cognitive performance compared to NBW pigs ( 19 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of impaired cognitive development is supported by earlier studies showing decreased learning and memory associated with LBW in pigs ( 17 , 18 ). Similarly, LBW in humans has been shown to cause learning difficulties throughout adolescence ( 6 , 7 ), as well as impaired spatial learning ( 47 ). However, there have also been studies which have shown LBW pigs to have a comparable, or even superior, cognitive performance compared to NBW pigs ( 19 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sub-optimal development of LBW offspring has been associated with postnatal cognitive impairments in a variety of species. In humans, LBW has been linked to learning difficulties throughout adolescence ( 6 , 7 ). Impaired cognitive development associated with LBW has also been studied in a variety of animal models, most frequently in rats and sheep [although contrary to pigs and humans, LBW has to be experimentally induced in these models—( 8 )].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low birth weight (LBW) is a known risk-factor for impaired cognitive and emotional development in humans. Children who were small for gestational age at birth are more likely to experience learning difficulties (O’Keeffe et al 2003; Yu and Garcy 2018) and show impaired academic performance (Strauss 2000; Larroque et al 2001; Lindström et al 2017) throughout childhood and adolescence. In terms of emotional development, lower birth weight is associated with increased likelihood of anxiety in adulthood (Lahti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…. On the same topic, Yu and Garcy report that individuals born small for gestational age had lower mean verbal, spatial and numerical test scores than those born appropriate or large for gestational age. In the accompanying editorial, Horowitz‐Kraus provides us with an insight into new techniques that can help to distinguish between different causes of reading challenges, even before a child has failed to read at school .…”
Section: Reading Difficulties Begin In the Wombmentioning
confidence: 99%